Oligomeric Receptor Complexes and Their Allosteric Receptor-Receptor Interactions in the Plasma Membrane Represent a New Biological Principle for Integration of Signals in the CNS - Borroto-Escuela, Dasiel O.; Fuxe, Kjell (Frontiers in Molecular Neuroscience, 2019)
GPCRs not only exist as monomers but also as homomers and heteromers in which allosteric receptor-receptor interactions take place modulating the functions of the participating GPCR protomers. GPCRs can also form heteroreceptor complexes with ionotropic receptors and receptor tyrosine kinases modulating their function. Furthermore, adaptor proteins interact with receptor protomers and modulate the interactions. The state of the art is that the allosteric receptor-receptor interactions are reciprocal, highly dynamic and substantially alter the signalling, trafficking, recognition and pharmacology of the participating protomers. The pattern of changes appears to be unique for each heteromer and can favour antagonistic or facilitatory interactions or switch the G protein coupling from e.g., Gi/o to Gq or to beta-arrestin signalling. It gives a new dimension to molecular integration in the nervous system. The future direction should be to determine the receptor interface involving building models of selected heterodimers. This will make it possible to design interface-interfering peptides that specifically disrupt the heterodimer. This will help to determine the functional role of the allosteric receptor-receptor interactions as well as the integration of signals at the plasma membrane by the heteroreceptor complexes versus integration of the intracellular signalling pathways. Integration of signals also at the plasma membrane seems crucial in view of the hypothesis that learning and memory at molecular level takes place by reorganization of homo and heteroreceptor complexes in the postsynaptic membrane. Homo and heteroreceptor complexes are in balance with each other, and their disbalance is linked to diseases. Targeting heteroreceptor complexes represents a novel strategy for treatment of brain disorders.